Cold War orientalism : Asia in the middlebrow imagination, 1945-1961 - Klein, Christina, 1963- (University of California Press, 2003)
This study reads the postwar period as one of international economic and political integration - a distinct chapter in the process of US-led globalization. It shows how US policy makers and intellectuals, created a global culture of integration that represented the growth of US power in Asia.